1993
DOI: 10.1128/mcb.13.4.2298
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of human zeta 2 globin promoter by the alpha globin regulatory element (HS-40): functional role of specific nuclear factor-DNA complexes.

Abstract: We studied the functional interaction between human embryonic C2 globin promoter and the a globin regulatory element region. These data suggest that transcriptional activation of human embryonic g2 globin gene and the fetal/adult a globin genes is mediated by erythroid cell-specific and developmental stage-specific nuclear factor-DNA complexes which form at the enhancer (HS-40) and the globin promoters.Similar to those of other vertebrates, the human ,3-and a-like globin gene families are each arranged as ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 42 publications
1
39
0
1
Order By: Relevance
“…At the same time, genomic footprinting analysis indicated that the AP1/NF-E2 motifs within several mammalian erythroid-speci®c regulatory elements including the locus-control-region of the human b globin locus or so-called b-globin-LCR (Figure 1), are occupied in vivo by factors in an erythroid lineage and developmental stage speci®c manner (Reddy and Shen, 1991;Ikuta and Kan, 1991;Zhang et al, 1993). However, due to the multiplicity of factor-recognition of the AP1/NF-E2 motif as mentioned above, it has been di cult to ascertain whether NF-E2, or another factor such as AP1, actually binds at these transcription regulatory elements on native chromatin in vivo.…”
Section: Abstract: Chromatin Immunoprecipitation; Ap1; Nf-e2; In Vivomentioning
confidence: 99%
“…At the same time, genomic footprinting analysis indicated that the AP1/NF-E2 motifs within several mammalian erythroid-speci®c regulatory elements including the locus-control-region of the human b globin locus or so-called b-globin-LCR (Figure 1), are occupied in vivo by factors in an erythroid lineage and developmental stage speci®c manner (Reddy and Shen, 1991;Ikuta and Kan, 1991;Zhang et al, 1993). However, due to the multiplicity of factor-recognition of the AP1/NF-E2 motif as mentioned above, it has been di cult to ascertain whether NF-E2, or another factor such as AP1, actually binds at these transcription regulatory elements on native chromatin in vivo.…”
Section: Abstract: Chromatin Immunoprecipitation; Ap1; Nf-e2; In Vivomentioning
confidence: 99%
“…Further remodeling and modification of the chromatin structure must occur in erythroid cells, however, since several new HS sites appear, including those at the HS-40 element and the promoter regions of the -and ␣-globin genes (54, 59). These latter sites apparently result from erythroid lineage-specific binding of nuclear factors to the above transcriptional regulatory elements, as demonstrated by previous genomic footprint analysis of 60) and of the ␣-globin upstream promoters (47).HS-40 acts as a classical enhancer in transient transfection assays (44,46,60), and it confers appropriate developmental control of the human -globin promoter activity in transgenic mice (19,23,45,56). In vitro and in vivo binding studies have shown that the HS-40 enhanceosome consists mainly of six DNA sequence motifs that are bound with nuclear factors in an erythroid lineage-specific manner: two NF-E2/AP1 motifs (5Ј-NA and 3Ј-NA), three GATA-1 motifs (b, c, and d), and a GT motif (26,50,60) (Fig.…”
mentioning
confidence: 77%
“…These latter sites apparently result from erythroid lineage-specific binding of nuclear factors to the above transcriptional regulatory elements, as demonstrated by previous genomic footprint analysis of 60) and of the ␣-globin upstream promoters (47).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The regulatory element α-MRE behaves as a classical enhancer; its main function in the normal chromosomal environment is to activate and enhance expression from the ζ-globin and the α-globin promoters (Zhang et al, 1993).…”
Section: The Human α-Major Regulatory Elementmentioning
confidence: 99%